Directions Robot: In-the-Wild Experiences and Lessons Learned - Bohus, Dan; Saw, Nick; Horvitz, Eric (2014)
We introduce Directions Robot, a system we have fielded for studying open-world human-robot interaction. The system brings together models for situated spoken language interaction with directions-generation and a gesturing humanoid robot. We describe the perceptual, interaction, and output generation competencies of this system. We then discuss experiences and lessons drawn from data collected in an initial in-the-wild deployment, and highlight several challenges with managing engagement, providing directions, and handling out-of-domain queries that arise in openworld, multiparty settings.